(untitled) (Revista Brasileira de Contabilidade e Gestão, 2018)
This essay has a theoretical-exploratory nature, and seeks to reflect on creative economy and creative industry, relating this reflection to the proposal of the PPGCIC - Postgraduate Program (Stricto Sensu - professional modality) in Communication and Creative Industry of Unipampa (São Borja campus), perceiving it as an environment for creative economics. This environment, where reflections and practical applications are developed on communication as a creative industry or for promotion from creative industry through communication techniques and practices. With this essay, we also seek to guide other approaches and broaden the scope of discussion about the creative economy.